IAPSM Position Paper on Vertical Transmission of HIV from Mother to Child - Dhrubajyoti J. Debnath; Sanjay K. Rai; Suchit Kamble; Nilesh Gawade; Meenal M Thakare; Purushottam Giri; Shubhada Suresh Javadekar (Indian Journal of Community Medicine)
Human immunodeficiency virus (HIV) can be transmitted through vertical route from the mother to her child during the period of pregnancy, process of childbirth, or through the breastfeeding. This is still a worldwide health issue, especially in environments with low resources. Without intervention, the transmission rate ranges from 15 to 45%, influenced by breastfeeding practices. Effective interventions, including antiretroviral therapy (ART), can reduce the transmission likelihood to about 2% with breastfeeding and 1% without breastfeeding. A further expansion of access to prevention of mother-to-child transmission of HIV (PMTCT) services was made possible by the year 2011 through the Global Plan toward the Elimination of New HIV Infections among Children and Keeping their Mothers Alive. By 2022, there were 130,000 new HIV infections in children under five, down from 310,000 in 2010. Nevertheless, the Joint United Nations Programme on HIV/AIDS (UNAIDS) Global Strategy to End AIDS’s 2025 targets cannot be met with the current level of progress. To prevent new infections in children, pregnant and breastfeeding women with HIV must receive faster medical attention. This position paper discusses the primary prevention of HIV and the healthcare system’s role in providing comprehensive care to HIV-positive women and their families. The continuum of care includes antenatal, intrapartum, post-delivery, and pediatric services, addressing the unique needs of each woman and her family. Individual-level interventions highlight the importance of partner selection, consistent condom use, avoiding needle sharing, and reducing risky sexual behaviors. Overcoming barriers to medication adherence, such as stigma and discrimination, is crucial for effective prevention and treatment. Community-level interventions are equally important in reducing stigma and discrimination and fostering healthcare-seeking behavior. The paper emphasizes a multi-faceted approach, involving healthcare systems, individuals, and communities, to accomplish the objective of an HIV-free generation by stopping HIV from spreading through the vertical route. Collaboration across these levels is essential to realizing this vision and ensuring optimal health outcomes for HIV-infected individuals, their children, and families.